A systematic review of health economic evaluations of proton beam therapy for adult cancer: Appraising methodology and quality. (January 2020) - Jones, David A.; Smith, Joel; Mei, Xue W.; Hawkins, Maria A.; Maughan, Tim; van den Heuvel, Frank; Mee, Thomas; Kirkby, Karen; Kirkby, Norman; Gray, Alastair
Highlights: The cost-effectiveness of PBT for adult cancers is subject to considerable uncertainty. Cost-utility analysis is the gold standard for assessing value, but quality matters. Our review found studies lacked external validation of model outcomes. When assessed against standard checklists, studies fell short. Improving transparency and validation will improve credibility of results. Abstract: Background and purpose: With high treatment costs and limited capacity, decisions on which adult patients to treat with proton beam therapy (PBT) must be based on the relative value compared to the current standard of care. Cost-utility analyses (CUAs) are the gold-standard method for doing this. We aimed to appraise the methodology and quality of CUAs in this area. Materials and Methods: We performed a systematic review of the literature to identify CUA studies of PBT in adult disease using MEDLINE, EMBASE, EconLIT, NHS Economic Evaluation Database (NHS EED), Web of Science, and the Tufts Medical Center Cost-Effectiveness Analysis Registry from 1st January 2010 up to 6th June 2018. General characteristics, information relating to modelling approaches, and methodological quality were extracted and synthesized narratively. Results: Seven PBT CUA studies in adult disease were identified. Without randomised controlled trials to inform the comparative effectiveness of PBT, studies used either results from one-armed studies, or dose-response models derived from radiobiological and epidemiological studies of PBT. Costing methods varied widely. The assessment of model quality highlighted a lack of transparency in the identification of model parameters, and absence of external validation of model outcomes. Furthermore, appropriate assessment of uncertainty was often deficient. Conclusion: In order to foster credibility, future CUA studies must be more systematic in their approach to evidence synthesis and expansive in their consideration of uncertainties in light of the lack of clinical evidence.